(untitled) (Muitas Vozes, 2021)
In this article, we analyze the construction [V1 + Ver], in which the position of V1, partially schematic, is filled by the verbs deixar (let), ir (go) and querer (want). Based on the theoretical-methodological apparatus of the Usage-Based Models (BYBEE, 2016; TRAUGOTT; TROUSDALE, 2013), our objective is to show that three related processes instantiate in the formation of the construction under analysis: “constructional change”, “constructionalization” and “(inter)subjectivization”. For this purpose, we use effective data on language usage extracted from contemporary Portuguese speech and writing samples and we characterize four types of constructions: (i) Constructions of movement with purpose; (ii) Periphrastic constructions; (iii) Modal constructions; and (iv) Discourse marker constructions. We show that the constructionalization of the “discourse marker” construction is the result of an increase in (inter)subjectivity, which is preceded by micro-steps of construction change.